Analisis Pembiayaan Sektor Perdagangan Hotel dan Restoran pada Perbankan Syariah di Indonesia - Geri Suryadi; Dominicus Savio Priyarsono; Laily Dwi Arsyianti (Department of Islamic Economics, IPB University, 2014)
Islamic banking is an alternative for entrepreneurs in trade, hotel, and restaurants (THR) to obtain capital relief that can push the pace of economic. The purpose of this study was to analyze the response of Islamic banking financing ratios on THR sector in the event of shocks to the banking performance factors, monetary instruments, macroeconomic conditions and the rate of return and analyze the contribution of each variable in explaining the diversity of Islamic financing ratios in THR sector. The analytical method used is Vector Error Correction Model (VECM) with variables that describe the performance of banking, macroeconomic conditions, monetary instruments, and financial returns. The results showed that, shocks to the variables Industrial Production Index (IPI), lending rates (SBK) and equivalent rate financing (ERP) will be responded positively by Islamic financing ratio of THR sector. While shocks to the variables of Third Party Funds (TPF), troubled financing (NPF), a bonus SBI Sharia (BSBIS), inflation (INF) and the placement of funds in the money market with Sharia principles (PUAS) will be responded negatively by Islamic financing ratio of THR sector. Based on this research, Islamic banking should be more focus on financing for the PHR sector because it will provide a great benefit to the development of the real sector.